Comparative pathogenicity of three A(H5N1) clade 2.3.4.4b HPAI viruses in blue-winged teal and transmission to domestic poultry - Tamiru N. Alkie; Carissa Embury-Hyatt; Anthony V. Signore; Frank Baldwin; Tamiko Hisanaga; Wanhong Xu; Estella Moffat; Jolene A. Giacinti; Catherine Soos; Yohannes Berhane (mSphere)
ABSTRACT Long-distance migratory ducks play a critical role in the maintenance and dissemination of A(H5N1) viruses. Comparative pathogenicity studies were conducted on blue-winged teal (BWTE; Anas discors) using three distinct genotypes of A(H5N1) clade 2.3.4.4b viruses (A1, B1.3, and B4.1) isolated from wild ducks in Canada. Twenty-four hours post-intranasal infection of BWTE, contact turkeys and chickens were introduced into each of the groups to evaluate viral transmission. The levels of viral shedding in BWTE increased from 3 to 7 days post-infection (dpi) and continued at lower levels until 14 dpi. The A1 genotype virus (MALL/NS/22) was found to be the least pathogenic to BWTE compared to the reassortant genotypes, B4.1 (RBME/BC/22) and B1.3 (BWTE/MB/22). The B1.3 genotype was the most virulent to BWTE and caused 66.7% mortality compared to 12.5% mortality caused by the B4.1 genotype. The extent of transmission from infected BWTE to contact turkeys and chickens showed variations. Turkeys housed with BWTE infected with either virus died within 6 to 10 days post-contact (dpc). Conversely, the transmission and mortality among contact chickens varied. The highest mortality (3 out of 5) occurred in chickens exposed to BWTE infected with the B1.3 genotype. Whilst in the B4.1 genotype, 2 out of 6 chickens died, none of the chickens in the A1 genotype succumbed to infection. No shedding or seroconversion was noted in all surviving chickens. This research underscores variations in the pathogenic traits and transmissibility among the different genotypes of A(H5N1) clade 2.3.4.4b viruses. This finding is vital for understanding the role of migratory birds in the epidemiology of A(H5N1) and the need for continuous monitoring of these viruses.IMPORTANCEThe recurrent incursions of A(H5N1) clade 2.3.4.4b viruses into North America have resulted in the emergence of reassortant virus genotypes. These genotypes exhibit variations in pathogenicity and host ranges. Blue-winged teal (BWTE) are the most common dabbling ducks in North America and play a crucial role in maintaining and dispersing influenza A viruses (IAVs). In some areas, the migratory pathways of BWTE overlap with densely populated commercial poultry facilities. Despite this, the role of BWTE in the maintenance and spread of A(H5N1) is not well understood, and there is limited data on their susceptibility to A(H5N1) clade 2.3.4.4b viruses. Our study demonstrates differences in BWTE susceptibility to distinct genotypes of A(H5N1) clade 2.3.4.4b viruses. The virus transmission from infected BWTE and lethality in turkeys and chickens were also influenced by the virus genotypes. The findings suggest that BWTE could contribute to the maintenance and spread of highly pathogenic avian influenza (HPAI) viruses, and active surveillance in BWTE is essential.